Pengaruh Pengungkapan Corporate Social Responsibility dan Penilaian Kinerja Perusahaan terhadap Return Saham (Studi pada perusahaan- perusahaan yang terdaftar di BEI) - Zakaria, Heikal Muhammad (UI Scholars Hub, 2016)
This study aims to see whether there is influence of Corporate Social Responsibility (CSR) disclosure according to Global Reporting Initiative (GRI) guidelines and corporate performance appraisal on stock returns. The magnitude of the CSR disclosure effect is measured by the CSR disclosure score of each dimension based on the GRI guidelines in the company report. In the measurement, the PEG Ratio is used to measure the company’s performance appraisal. Hypothesis testing is done using multiple regression model and partial with sample of 50 companies listed in BEI in year 2013. The results of this study provide empirical evidence that (1) CSR disclosure and corporate performance appraisal have a mutual effect on Stock Return (2) CSR disclosure have a positive and significant effect on stock return (3) company performance assessment proxy with PEG ratios have positive influence and significant to Stock Return.